[PP.16.09] SMOKING HABIT AND CARDIOVASCULAR RISK PROFILE IN ELDERLY OUTPATIENTS. (September 2016) - Marotta, T.; De Mitri, A.; Ferrara, L.A.
Abstract : Objective: To assess the association of smoking habit with demographics and other cardiovascular risk factors in elderly outpatients. Design and method: Demographics and lifestyle of 884 outpatients (76% women) over 60 years, attending the Internal Medicine Clinic of two public facilities located in deprived districts of Naples, were assessed by a structured questionnaire. χ 2, Wilcoxon, and Student t tests were performed as appropriate. Results: 216 patients (16.4% of total) were smokers and 668 (83.6%) were non-smokers. Smokers represented 20.8% of men and 15.0% of women (p < 0.05). They were slightly younger (66.6 ± 6 vs 67.7 ± 6, p < 0.04), had less children (2.9 ± 1.9 vs 3.6 ± 2.4, p = 0.005) and were better educated (p < 0.04) than non-smokers, in the general context of a low educational level. Smoking habit was associated with coffee intake (p < 0.001), but not with alcohol consumption, nor with sedentary aptitude. Hypertension was more prevalent in non-smokers (79.2%) than in smokers (69.7%, p < 0.02); conversely, 22.2% of normotensives, but only 14.7% of hypertensives were current smokers. Quitting cigarettes was more common among hypertensives (67.0% of smokers) than among normotensives (56.0%, p < 0.05). Obesity (13.1%) and impaired glucose metabolism (12.9%) were also associated with a lower prevalence of smoking habit, as compared to the absence of obesity (23.1%, p < 0.001) and normal glucose metabolism, respectively (18.0%, p = 0.056). A separate analysis confirmed the uneven coffee consumption between smokers and non-smokers in both genders, but the other differences were significant only in women. In addition, smokers were less numerous among diabetic women than among non-diabetic women (7.5% vs 16.5 %, p < 0.02). Conclusions: In this elderly outpatient population, smoking habit is linked to socioeconomic and lifestyle pattern. The presence of other cardiovascular risk factors, such as hypertension, diabetes, and obesity, probably acts as a deterrent, which discourages patients from smoking and favours quitting. This finding suggests that, even in an environment of low socioeconomic level, medical advise and public anti-smoke campaigns have been effective in helping patients to avoid smoking, at least in the presence of concomitant cardiovascular risk factors. It is desirable that a message just as convincing is also delivered to people without metabolic abnormalities.